2018
DOI: 10.3233/jad-170826
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Verb Fluency in the Detection of Early Cognitive Impairment in Alzheimer’s Disease

Abstract: The VF test may be a useful tool for the differential diagnosis of cognitive failure in the elderly. Since VF deficits seem to take place in early stages of the disease, it is a suitable neuropsychological tool for the detection not only of CH people who will convert to MCI, but also from MCI to dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 61 publications
5
29
0
3
Order By: Relevance
“…For instance, verb fluency (originally referred to as action fluency; see Piatt et al, 1999 for validity;Woods et al, 2005 for normative data) appears sensitive to cognitive deficits stemming from frontal-striatal impairments (Kochhann et al, 2018). Indeed, individuals with mild cognitive impairment (MCI) or subjective cognitive decline (SCD) have been found to show impaired verb fluency performance (Östberg et al, 2005Forlenza et al, 2012;Alegret et al, 2018;Macoir et al, 2019) as have individuals with Alzheimer's disease (AD; Östberg et al, 2007;McDowd et al, 2011;Beber et al, 2015;Dubois et al, 2016;Alegret et al, 2018) and individuals with Parkinson's disease (PD) dementia (Piatt et al, 1999). Verb fluency tasks have also been used to predict dementia severity (e.g., Lai and Lin, 2013) and aid in the differential diagnosis of frontotemporal lobar degeneration (FTLD) vs.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, verb fluency (originally referred to as action fluency; see Piatt et al, 1999 for validity;Woods et al, 2005 for normative data) appears sensitive to cognitive deficits stemming from frontal-striatal impairments (Kochhann et al, 2018). Indeed, individuals with mild cognitive impairment (MCI) or subjective cognitive decline (SCD) have been found to show impaired verb fluency performance (Östberg et al, 2005Forlenza et al, 2012;Alegret et al, 2018;Macoir et al, 2019) as have individuals with Alzheimer's disease (AD; Östberg et al, 2007;McDowd et al, 2011;Beber et al, 2015;Dubois et al, 2016;Alegret et al, 2018) and individuals with Parkinson's disease (PD) dementia (Piatt et al, 1999). Verb fluency tasks have also been used to predict dementia severity (e.g., Lai and Lin, 2013) and aid in the differential diagnosis of frontotemporal lobar degeneration (FTLD) vs.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is potential for future work examining longitudinal associations. For example, processing speed and executive function have been shown to be more sensitive to cognitive decline among Hispanic/Latino adults compared with Whites [43,44]. The present study provides initial evidence on factors associated with enhanced executive functioning and processing speed, but further investigation is warranted.…”
Section: Discussionmentioning
confidence: 68%
“…(2) Chinese Version Verbal Learning Test (CVVLT), in which the proposed cutoff point of total score between HC and dementia was 20/21 (Chang et al, 2010); (3) Logic Memory (LM) Test of Wechsler Memory Scale, which has been shown to be a sensitive measure for detecting MCI and AD (Rabin et al, 2009); (4) Boston Naming Test, whose normative data from geriatric performance has been established (Jefferson et al, 2007); (5) Rey-Osterrieth Complex Figure Test, with the proposed cutoff score delayed recall subscale between HC and MCI of 18/19 (Takayama, 2010); (6) Trail Making Test Part A and B, whose psychometric properties have also been established in Chinese version (Wei et al, 2018); (7) Digit Span Forward and Backward Test (Muangpaisan et al, 2010); and (8) Verbal Fluency Test, with the proposed cutoff score between HC and those with cognitive impairments (MCI and mild dementia) of 16/17 (Alegret et al, 2018). Apolipoprotein E ε4 (APOE 4) genotyping was also performed in all subjects.…”
Section: Neuropsychological Testingmentioning
confidence: 99%